Componentes vasculares e neurais da retina em indivíduos com deficiência isolada do hormônio de crescimento - Menezes, Nelmo Vasconcelos de (2022)
The somatotropic axis, including hypothalamic growth hormone (GH) releasing hormone (GHRH), pituitary GH, and circulating insulin-like growth factor I (IGF-I), is critical to body size. However, local production of GH/IGF-I (and IGF-II) and other peptides are relevant to other body functions such as vascular, brain and retinal functions. The consequences of GH deficiency (GHD) on the retinal structure are still unclear, possibly reflecting the heterogeneity of patients and the different types of assessment in previous publications. Objectives: To evaluate quantitative measurements of the vascular and neural components of the retina in individuals with congenital deficiency growth hormone (IDGH), as well as to evaluate the variables of optical coherence tomography (OCT) of the retina and optic nerve and OCT-angiography (OCTA) in individuals with IDGH. Methodology: A cross-sectional study was performed with 25 adult patients with IDGH matched with another 25 controls matched by age and sex. To obtain the necessary information, interviews, physical examination, laboratory workup, OCT and OCTA were performed. Results: No difference was found by OCT in the middle areas of the nerve fiber layer, nor in the areas of the upper, lower or nasal quadrants, between the two groups. However, the areas of the temporal quadrant (p=0.041), the optic disc (p=0.042), the cup (p<0.0001), as well as the cup/disc ratio (p<0.0001), were higher in subjects with IDGH than in controls. The rim area was smaller (p=0.002), although still normal. In OCTA, there was no difference in minimum foveal thickness, central fovea, foveal avascular zone and retinal density in any evaluated area between the two groups. Conclusion: DIGH appears to enlarge the optic disc but does not affect quantitative measures of the vascular and neural retina.